2000
DOI: 10.1172/jci9944
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites from apoptotic thymocytes inhibit thymopoiesis in adenosine deaminase–deficient fetal thymic organ cultures

Abstract: Murine fetal thymic organ culture was used to investigate the mechanism by which adenosine deaminase (ADA) deficiency causes T-cell immunodeficiency. C57BL/6 fetal thymuses treated with the specific ADA inhibitor 2′-deoxycoformycin exhibited features of the human disease, including accumulation of dATP and inhibition of S-adenosylhomocysteine hydrolase enzyme activity. Although T-cell receptor (TCR) Vβ gene rearrangements and pre-TCR-α expression were normal in ADA-deficient cultures, the production of αβ TCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 39 publications
4
36
0
Order By: Relevance
“…An investigation of the B cell compartment in the bone marrow of ADA-deficient mice was initiated to determine whether, in analogy to T cell development, a blockade in B cell lymphopoiesis exists (5,16,17). The developmental parallels showed by B and T cells, including gene rearrangement and selection, suggested that ADA deficiency, with a block in early T cell development, could equally affect the early B cell maturation program.…”
Section: B Cell Development In Bone Marrow Is Not Impaired In Ada-defmentioning
confidence: 99%
“…An investigation of the B cell compartment in the bone marrow of ADA-deficient mice was initiated to determine whether, in analogy to T cell development, a blockade in B cell lymphopoiesis exists (5,16,17). The developmental parallels showed by B and T cells, including gene rearrangement and selection, suggested that ADA deficiency, with a block in early T cell development, could equally affect the early B cell maturation program.…”
Section: B Cell Development In Bone Marrow Is Not Impaired In Ada-defmentioning
confidence: 99%
“…ADA-deficient murine fetal thymic organ culture (FTOC) is an excellent model of the human disease (12) because it exhibits many biochemical features of ADA-deficient patients, including ADA substrate and dATP accumulation as well as S-adenosylhomocysteine (SAH) hydrolase inhibition. Furthermore, the yield of thymocytes from ADA-deficient cultures is 85-95% less than in control cultures, with thymocyte development becoming progressively more impaired past the CD4 -CD8 -CD25 + CD44 -stage, the point where T cell receptor β (TCRβ) V→DJ gene rearrangements occur.…”
Section: Introductionmentioning
confidence: 99%
“…In the thymus, where the normal process of T cell development results in extensive cell death, extracellular DNA and high levels of deoxynucleoside kinases together create a persistent source of dATP (3). In the absence of ADA, increased intracellular dATP levels interfere with cellular metabolism, promote mitochondrial cytochrome c release, and ultimately cause apoptosis (3)(4)(5). Thus, ADA knockout mice suffer from pronounced T cell defects.…”
mentioning
confidence: 99%